أثر الانفاق الحكومي علي سعر الصرف في السودان خلال الفترة من - د. محمد عبد الله محمد أحمد (White Nile Journal for Studies and Research, 2024)
The paper aimed to study the impact of government expenditure on the exchange rate in Sudan during the period from (2000-2022 AD). The paper followed the econometrics approach through the linear regression model on time series data. The paper's hypotheses were that there is a relationship between government expenditure and the exchange rate. The paper reached the most important results, which are that government expenditure has a direct and positive effect on the exchange rate. The most important recommendations were the need to pay attention to increasing government expenditure on infrastructure and productive activity that contributes to expanding the productive capacity of the economy. When formulating the exchange rate policy ،the impact of government expenditure on the exchange rate must be taken into account ،because it leads to the depletion of a large part of income in spending on imports at the expense of local production, which may have negative effects on the exchange rate.